"Paradigm Shift": An Investigation of Preservice Teachers' Perceptions of Teaching English as an International Language - Liping Wei (Cranmore Publishing, 2019)
The unprecedented use of English as a means of international and intercultural communication around the world has made it increasingly unrealistic and inappropriate to hold to the native speaker norms. This paper examines preservice teachers' perceptions of teaching English as an International Language (EIL), employing qualitative methods. The participants were 31 teacher candidates enrolled in an undergraduate course "Teaching English as a Second Language" in the teacher education program of a public university in a Southwestern State of the U.S. The data sources included online postings, interview transcripts, and synthesis papers. This study revealed that although the participants were all aware of the heterogeneity of the English language and were willing to promote multilingualism, the majority of them still clung to the notion that "Standard" English is the only variety of English that should be taught in the classroom. This paper maintains that in order to raise classroom teachers' awareness of teaching EIL, teacher educators should demolish American or British English as the orthodox and establish a new pedagogic model that de-emphasizes the native speaker norms and embraces all varieties of the English language.